Persepsi pendeta GMIM Viadolorosa mengenai pencegahan kekerasan terhadap perempuan - Aruperes, Novelia; Ratag, Gustaaf A. E.; Rombot, Dina V. (JURNAL KEDOKTERAN KOMUNITAS DAN TROPIK, 2016)
Objective: To investigate the perceptions of the priests about prevention of violence against women. Method: This is a descriptive qualitative study, with grounded theory as the research type. Results: The informants had a good understanding of violence, types of violence, the impact of violence, prevention of violence, efforts in preventing violence, and obstacles faced by the priests in preventing violence against women. Conclusion: Priests of GMIM Viadolorosa in Kairagi Dua have good perception and acceptance on violence against women. Keywords: perception, priest, prevention of violence against women